A Large Sporadic Intra-abdominal Desmoid-Type Fibromatosis in a Young Male: A Case Report - Sioda, Natasha A.; Wakim, Andre A.; Wong, Tina; Patel, Shyamal; Coan, Kathryn; Row, David (Frontiers in Surgery, 2020)
Desmoid type fibromatosis (DTF) is a rare benign tumor of connective tissue origin. While these tumors are typically not malignant, they can exhibit aggressive growth patterns causing mass effect on surrounding organs. Due to the rarity of this tumor, there is limited medical literature surrounding the prognosis, recurrence, and treatment efficacy of these tumors. We present a case of a young male with a sporadic 31 x 25 x 12 cm DTF complicated by mass effect on bowel and intra-abdominal organs requiring surgical intervention. The patient presented with weight gain and abdominal pressure. Abdominal distension without tenderness on palpation was noted on physical examination. The tumor biopsy confirmed the diagnosis of DTF. No evidence of familial adenomatous polyposis or Gardner syndrome was identified. The tumor was surgically excised and intimately associated with the bowel requiring ileocolonic resection with primary anastomosis. At three-month follow up, surveillance MRI showed no residual or recurrent lesion. To our knowledge, this is the largest sporadic intra-abdominal DTF reported in the literature. A multi-disciplinary approach to this patient’s diagnosis and treatment allowed for an accurate diagnosis, efficient treatment and follow up plan.